Pelatihan Berbasis Proteus untuk Meningkatkan Keterampilan Elektronika Siswa SMK Muhammadiyah 2 Metro - Rhahmi Adni Pesma; Joni Joni; Achmad Chalid Afif Alfajrin; Kisna Pertiwi; Yusuf Affandi (Pusat Riset dan Inovasi Nasional, 2026)
This community service activity was carried out at SMK Muhammadiyah 2 Metro with the aim of enhancing students' electronics skills through training based on the Proteus simulation application. The program was designed to enrich the learning experience of practical electronics circuits by combining physical circuits used in the school with software-assisted simulations. The activities included needs analysis, preparation of modules and practical worksheets, a Proteus introduction workshop, and guided practice sessions for designing and simulating circuits. Evaluation was conducted through pre- and post-training tests, as well as classroom observations, which showed an improvement in students' understanding of basic electronics concepts and their ability to design and simulate circuits. In addition, teachers received modules and examples of practical scenarios that can be integrated into regular lessons. Overall, this Proteus-based training proved to be an effective alternative media for practical electronics learning at SMK. The program not only improved students' technical skills but also opened the possibility of being applied to other relevant areas of expertise. With the success achieved, this program has the potential to be replicated in other schools with similar curricula to further enhance the quality of practical learning in electronics.